Pengaruh Konflik Pekerjaan Keluarga, Kejenuhan Kerja, Dan Lingkungan Kerja Terhadap Kinerja Perawat RSUD Batin Mangunang Kota Agung - Adhari; Yuningsih (Shofanah Media Berkah, 2025)
This study aims to examine the influence of work-family conflict, job burnout, and work environment on the performance of nurses at RSUD Batin Mangunang Kotaagung. The study involved 126 respondents as the sample. This is a quantitative study, and the sample was selected using probability sampling with the simple random sampling technique. The analysis of each variable employed various testing tools, including validity tests, reliability tests, normality tests, multiple linear regression analysis, and partial t-tests. The results of the study revealed that work-family conflict and work environment positively and significantly influence performance, whereas job burnout negatively and significantly affects performance. These findings indicate that while role conflicts may, in some conditions, drive performance improvement, job burnout remains a weakening factor, and a good work environment serves as a key supporter of enhanced performance. Based on these findings, nurses are encouraged to manage their time using structured schedules, improve stress management skills through relaxation techniques and mindfulness, and proactively report insufficient or substandard work tools. RSUD Batin Mangunang Kotaagung is expected to provide flexible work schedules, offer counseling or stress management training programs, regularly evaluate workloads and the quality of tools, and ensure the procurement of tools that meet quality standards. These measures aim to create a conducive work environment, enhance the emotional well-being of nurses, and support efficiency and the achievement of work standards.